2016
DOI: 10.1021/acs.energyfuels.6b01556
|View full text |Cite
|
Sign up to set email alerts
|

Study on Reduced Chemical Mechanisms of Ammonia/Methane Combustion under Gas Turbine Conditions

Abstract: As an alternative fuel and hydrogen carrier, ammonia is believed to have good potential for future power generation. To explore the feasibility of co-firing ammonia with methane, studies involving robust numerical analyses with detailed chemistry are required to progress toward industrial implementation. Therefore, the objective of this study is to determine a reduced mechanism for simulation studies of ammonia/methane combustion in practical gas turbine combustor conditions. First, five different-sized reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(36 citation statements)
references
References 31 publications
0
36
0
Order By: Relevance
“…The analysis was carried out using 5 different reaction mechanisms, selecting those that show the most promising results for the study of ammonia/hydrogen gas turbines as done by Xiao et al [29]. A redu ed odel of Ko o 's mechanism [23], Tia 's [30], Mathieu's [31], Klippe stei 's [32], a d Miller's [33] were used for the study, Figure 2. The results demonstrate that the flame speed of a 50:50 ammonia/hydrogen blend is close to that produced by methane [34][35] under lean conditions espe ially usi g Tia 's odel.…”
Section: = √mentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis was carried out using 5 different reaction mechanisms, selecting those that show the most promising results for the study of ammonia/hydrogen gas turbines as done by Xiao et al [29]. A redu ed odel of Ko o 's mechanism [23], Tia 's [30], Mathieu's [31], Klippe stei 's [32], a d Miller's [33] were used for the study, Figure 2. The results demonstrate that the flame speed of a 50:50 ammonia/hydrogen blend is close to that produced by methane [34][35] under lean conditions espe ially usi g Tia 's odel.…”
Section: = √mentioning
confidence: 99%
“…It was found that NOx and CO emissions were considerably low at high equivalence ratios >1.10, identifying a region of chemically reactive balance between methane and ammonia combustion. Xiao et al [23] have also assessed the potential of using ammonia/methane blends for power generation. Using the Konnov reaction mechanism, a 2D numerical study was undertaken to determine the characteristics of methane/ammonia blends and their combustion characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The reason to select this mixture as a realistic case study is that ammonia is a useful chemical commodity and has received lots of attention both in academia and industry [45][46][47][48][49][50][51]. It is also a promising alternative medium for energy storage and transportation [52][53][54][55]. Industrial ammonia synthesis is carried out using the Haber-Bosch process with heterogeneous iron or ruthenium catalysts at high temperatures (623-873 K) and at a pressure range of 20-40 MPa [56][57][58].…”
Section: Introductionmentioning
confidence: 99%
“…These kinetic models have proven reasonable accuracy for ammonia/hydrogen combustion under certain laboratory conditions. 43−47 However, due to the lack of a comprehensive study and experimental verification, 29,48 the applicability of the mechanisms for practical combustion of ammonia-based fuels still needs to be developed and improved, particularly for industrially relevant conditions.…”
Section: Introductionmentioning
confidence: 99%